POEM IN 78 R.P.M.: THE RHYTHM OF JAZZ IN THE POETRY OF ALLEN GINSBERG AND ROBERTO PIVA - Lochini, Patricia [UNESP]; Andrade, Paulo [UNESP] (Univ Estadual Mato Grosso Sul, 2019)
The rhythm is not merely a formal resource, but is intimately connected with the sensitivity of man, reflecting all his uneasiness. As Candido (2006) states, the diffusion of jazz generalizes by the classes of Western society an orchestral rhythm reentronized in triumph and violent syncopation, because, from its dissonant system, it defines the sensibility of a ravaged society to the chaos of modernity. Jazz, in its essence, does not seek the refinement of sound, but rather an accumulation of it, culminating in an anarchy of sound. The chaotic context is conducive to the adoption of a posture opposed to reason, using as an intermediary delusion as a rupture of the individual with the socially instituted rationalist logic. This utopian sensibility is present both in jazz and in modern poetry: the manifesto of the suffering of the fall of man in a saxophone cry. In this way, we aim to analyze how two poets of the twentieth century, Allen Ginsberg and Roberto Piva, in their respective works Howl and other poems (1956) and Paranoia (1963), explore the language of jazz in their verses, in order to express the revolt of the subject in relation to the abstract rationalization of modern society, through the free expression of its original impulses.
Keywords: jazz; modern poetry; prosody; resistance